Antioxidant Blend of Curcumin and Broccoli Seed Extract Exhibits Protective Effect on Neurodegeneration and Promotes Drosophila Lifespan. (May 2021) - Cheng, Jingjing; Wang, Honglei; Bartlett, Mark; Stevenson, Douglas; Pan, Yufeng; Ho, Margaret S.; Ren, Yiping
Antioxidants and related compounds are anti-inflammatory and exhibit great potential in promoting human health. They are also often considered to be important elements in the process of neurodegeneration. Here we describe a antioxidant blend of Curcumin and Broccoli Seed Extract (BSE). Flies treated with the blend exhibit extended lifespan. RNA-seq analysis of samples from adult fly brains reveals a wide array of new genes with differential expression upon treatment with the blend. Interestingly, abolishing expression of some of the identified genes in dopaminergic (DA) neurons does not affect DA neuron number. Taken together, our findings reveal an antioxidant blend that promotes fly longevity and exhibits protective effect over neurodegeneration, demonstrating the importance of antioxidants in health and pathology.